Sexuality and intimacy among people with serious mental illness in hospital and community settings: a systematic review of qualitative research - Mc Cann, Edward; Eustace-Cook, Jessica; Donohue, Grainne; Nugter, Annet; Stewart, Jessica (My University, 2018)
Objective: The aim of this systematic review was to synthesize the best available qualitative evidence on the experiences and support needs of people with serious mental illness (SMI) regarding sexuality and intimacy within hospital and community settings. The objectives were to explore intimate relationship experiences of people with SMI, to uncover potential obstacles to the expression of sexuality and to present recommendations for mental health policy, education, research and practice. Introduction: Mental health services worldwide have seen major transformations in recent years through deinstitutionalization programs and more enlightened ways of organizing and providing mental health care. However, in terms of social and emotional wellbeing, issues persist for people with SMI, particularly relating to intimacy and the expression of sexuality. This systematic review may assist service providers to determine ways that they may better support people in establishing and maintaining satisfying intimate relationships and the full expression of their sexuality. Inclusion criteria: This review explored the intimacy and sexuality experiences, perceptions and concerns of people over the age of 18 years who were living with a SMI in hospital or community settings. This review considered studies that focused on qualitative data including, but not limited to, designs such as phenomenology, grounded theory, ethnography, action research and feminist research. Methods: The databases MEDLINE, CINAHL, PsycINFO, Embase and Web of Science were utilised in the review. The search included studies published from 1995 up to and including February 6, 2018 and were limited to those in the English language. Each paper was assessed by two independent reviewers for methodological quality using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Qualitative Research. Any disagreements that arose between the reviewers were resolved through discussion. Data extraction was conducted by two independent reviewers using the standardized qualitative data extraction tool from JBI. The qualitative research findings were pooled using JBI methodology. The JBI process of meta-aggregation was used to identify categories and synthesized findings. Results: Based on the thematic findings from the 21 studies, three synthesized findings were extracted from 10 categories and 83 findings: 1) the complexity of individual sexual experiences, 2) the clinical constructs of sexuality and 3) family and partner involvement. Conclusions: Having fulfilling and satisfying sexual and relationship experiences is a fundamental human right that can enhance an individual's quality of life. Being aware of the potential stresses and challenges that having a SMI can have on a relationship and involving partners in the treatment, may help to promote intimacy and recovery. Practitioners can use these findings to guide future policy, education and developments in practice. Further research is required to develop and evaluate interventions that target the identified barriers and help people with SMI to fulfil their unmet sexuality and intimacy needs.
PUBLISHED
Keywords: Serious mental illness; Intimacy; Qualitative; Sexuality; Inclusive Society; MENTAL HEALTH; Mental Health Practice; Recovery in Mental Health; Schizophrenia